Effects of a single bout of strenuous exercise on platelet activation in female ApoE/LDLR−/− mice. (3rd October 2017) - Przyborowski, K.; Kassassir, H.; Wojewoda, M.; Kmiecik, K.; Sitek, B.; Siewiera, K.; Zakrzewska, A.; Rudolf, A. M.; Kostogrys, R.; Watala, C.; Zoladz, J. A.; Chlopicki, S.
Abstract: Strenuous physical exercise leads to platelet activation that is normally counterbalanced by the production of endothelium-derived anti-platelet mediators, including prostacyclin (PGI2 ) and nitric oxide (NO). However, in the case of endothelial dysfunction, e.g. in atherosclerosis, there exists an increased risk for intravascular thrombosis during exercise that might be due to an impairment in endothelial anti-platelet mechanisms. In the present work, we evaluated platelet activation at rest and following a single bout of strenuous treadmill exercise in female ApoE/LDLR − /− mice with early (3-month-old) and advanced (7-month-old) atherosclerosis compared to female age-matched WT mice. In sedentary and post-exercise groups of animals, we analyzed TXB2 generation and the expression of platelet activation markers in the whole blood ex vivo assay. We also measured pre- and post-exercise plasma concentration of 6-keto-PGF1α, nitrite/nitrate, lipid profile, and blood cell count. Sedentary 3- and 7-month-old ApoE/LDLR − /− mice displayed significantly higher activation of platelets compared to age-matched wild-type (WT) mice, as evidenced by increased TXB2 production, expression of P-selectin, and activation of GPIIb/IIIa receptors, as well as increased fibrinogen and von Willebrand factor (vWf) binding. Interestingly, in ApoE/LDLR − /− but not in WT mice, strenuous exercise partially inhibited TXB2 production, the expression of activated GPIIb/IIIa receptors, and fibrinogen binding, with no effect on the P-selectin expression and vWf binding. Post-exercise down-regulation of the activated GPIIb/IIIa receptor expression and fibrinogen binding was not significantly different between 3- and 7-month-old ApoE/LDLR − /− mice; however, only 7-month-old ApoE/LDLR − /− mice showed lower TXB2 production after exercise. In female 4–6-month-old ApoE/LDLR − /− but not in WT mice, an elevated pre- and post-exercise plasma concentration of 6-keto-PGF1α was observed. In turn, the pre- and post-exercise plasma concentrations of nitrite (NO2 − ) and nitrate (NO3 − ) were decreased in ApoE/LDLR − /− as compared to that in age-matched WT mice. In conclusion, we demonstrated overactivation of platelets in ApoE/LDLR − /− as compared to WT mice. However, platelet activation in ApoE/LDLR − /− mice was not further increased by strenuous exercise, but was instead attenuated, a phenomenon not observed in WT mice. This phenomenon could be linked to compensatory up-regulation of PGI2 -dependent anti-platelet mechanisms in ApoE/LDLR − /− mice.